Identifying research priorities for occupational therapy in the UK: A James Lind Alliance Priority Setting Partnership. (December 2021) - Watson, Jo; Cowan, Katherine; Spring, Hannah; Donnell, Jenny Mac; Unstead-Joss, Ruth
Introduction: As the scope and nature of practice evolves in an ever-changing health and social care landscape, it is imperative the profession continues to expand the evidence base underpinning interventions. The Royal College of Occupational Therapists partnered with the James Lind Alliance to bring together people with lived experience, occupational therapists and other people working in the health and care sector to identify contemporary research priorities for the profession in the United Kingdom. Method: The JLA's well-established methodology was adopted. An opening consultation survey gathered unanswered questions. Analysis of responses and evidence checking preceded an initial prioritisation survey. The final prioritisation workshop drew on nominal group technique. Findings: 927 respondents submitted 2193 questions. Those within the project's scope were captured in 66 overarching summary questions using thematic analysis. These were initially ranked by 1140 respondents. 18 questions comprising the 10 most highly ranked by people with lived experience and by those with professional experience were considered by 19 participants in the final workshop. Together, they reached consensus on the Top 10 priorities. Conclusion: These research priorities provide a contemporary framework influencing and guiding future research, ensuring it addresses the issues of greatest importance to people accessing and delivering services.